AI-Enhanced Cloud ETL for Real-Time Health Data Processing: Transforming Healthcare through Intelligent Data Management - Ravi Kumar Amaresam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-Enhanced Cloud ETL systems represent a transformative solution for healthcare organizations facing unprecedented challenges in managing explosive growth of patient data. By combining cloud computing with artificial intelligence capabilities, these next-generation frameworks enable healthcare providers to bridge the gap between data collection and meaningful utilization. The implementation of these advanced data processing architectures allows for real-time streaming, reducing data latency from hours to seconds for critical clinical information. Organizations utilizing these systems experience significant improvements in diagnostic accuracy, reduction in hospital readmission rates, and substantial cost savings through efficient resource allocation and reduced administrative overhead. Beyond technical improvements, these platforms fundamentally change how healthcare data can be leveraged across the care continuum, enabling personalized medicine, population health management at scale, and proactive care delivery models. As healthcare continues its transformation into a data-driven industry, organizations implementing these advanced data processing capabilities are uniquely positioned to deliver superior patient outcomes, operational efficiency, and breakthrough clinical innovations while addressing challenges related to data security, legacy system integration, model accuracy, and regulatory compliance.